Adwa, an African victory - Gerima, Haile; Cubano, Agustin; Astatke, Mulatu, 1943-; Bailey, Albert; Negod-Gwad Productions; Mypheduh Films ([Washington, DC] : Mypheduh Films, Inc. [distributor], 2003)
On March 2, 1896, the Italians embarked on the final European conquest of an African nation, Ethiopia. With brilliant military intelligence and gallant generals at the helm, united and willed, the Ethiopian people fought their way to triumph over the Italians at the Battle of Adwa. The event ignited a lasting flame of hope, of freedom and independence in the hearts of African throughout the world. Haile Gerima, the director and producer, joins the voices of Ethiopian historians, elders, priests, poets and singers, capturing on film the powerful education and experience that shaped his consciousness. In a collage of Ethiopian landscapes, paintings, photographs and faces, the film illuminates one of the hidden sources of African empowerment.
DVD; mono.
In English and Amharic.
Produced, directed and edited by Haile Gerima ; production manager, Solomon Bekele ; director of cinematography, Agustin Cubano ; sound, Albert Bailey ; traditional music arranged by Mulatu Astatke.
Originally produced as a motion picture in 1999.
Keywords: Documentary films; Documentary films -- Ethiopia; Documentary films -- Africa; Documentary films -- Italy; War films -- Ethiopia; Historical films -- Ethiopia; Independent films -- Ethiopia; Adwa, Battle of, Adwa, Ethiopia, 1896.; Menelik -- II, -- Emperor of Ethiopia, -- 1844-1913.; Taitu, -- Empress, consort of Menelik II, Negus of Ethiopia, -- -1918.; Italo-Ethiopian War, 1895-1896.; Ethiopia -- History -- 1889-1974.